VP29 Organizational Aspects In Health Technology Assessment: A New Approach For Future Assessments. (12th January 2018) - Specchia, Maria Lucia; Cacciatore, Pasquale; Mazzotta, Francesco; Ricciardi, Walter; Damiani, Gianfranco
Abstract : INTRODUCTION: Organizational aspects influence the behavior of healthcare professionals and managers, and may help to overcome the barriers in the implementation of new health technologies. However, the organizational domain is often under-represented or absent when Health Technology Assessment (HTA) reports are built. The objective of this study was to to explore the organizational assessment in HTA and build a new framework for applicative experience after the comparison with the European Network for HTA (EUnetHTA's) CoreModel 3.0. METHODS: A literature review was performed by extracting full HTA reports through INAHTA (International Network of Agencies for Health Technology Assessment) members websites, HTA agencies and snowball search, and the aspects relating to the organizational assessment were analyzed. A quantitative and qualitative analysis was performed on the retrieved reports and the results were compared with a framework of five domains and fifteen subdomains from EUnetHTA's CoreModel 3.0. A Multiple Correspondence Analysis was carried out in order to evaluate the power of CoreModel and identify new common domains to guide the organizational assessments in HTA reports. RESULTS: The assessments of organizational issues in the reports were significantly heterogeneous and less common than inclusion of other classic assessments. When included, domains and subdomains of the CoreModel were not covered homogeneously by the organizational assessments (representation level varied from 19 percent to 62 percent). The statistical analysis performed on the current data and the subsequent clustering of items offered the possibility to develop a new methodology based on three new composite indicators. CONCLUSIONS: This ongoing study analyzed the relevance of organizational assessments in current literature and the challenges of promoting an international approach to the matter. In this sense, according to the current state of the research, we proposed a new methodology to cover the most relevant aspects of organizational appraisal according to new, more homogeneous domains and a less context-oriented approach to encourage health professionals to perform organizational analysis and better fulfill the needs of future HTA research.